The implementation of corporate governance principles in an emerging economy: a critique of the situation in Cyprus - Psaros, Jim; Krambia-Kapardis, Maria; Psaros, Jim (My University, 2006)
Abstract When the Cyprus economy was booming in the 1990s, key issues emanating from sound corporate governance, such as accountability, transparency and effective independent boards were not deemed important. However, largely as a result of the Cyprus stock exchange collapse of 2000, this view changed. In September 2002, due to the collapse, the Cyprus Stock Exchange implemented a Corporate Governance Code predicated largely on Anglo-Saxon principles of corporate governance. This paper reports the result of a study into levels of compliance with the Code by companies listed on the Cyprus Stock Exchange. The findings indicate that only a small minority complied with all significant aspects of the Code, and the vast majority did not comply with any. While the Code was well intended, the intended reforms do not appear to have significantly improved corporate governance. This is perhaps not surprising, given that the Cyprus equity markets and corresponding legislative support pertaining to corporate governance are in their infancy. In addition, some typical free market controls (e.g. low degree of concentration of ownership, reliable and timely information flows and opportunities for investor diversification) that facilitate international institutional investment do not exist in Cyprus. This suggests that the introduction of a Corporate Governance Code in Cyprus, or other developing economies, is likely to have only minimal impact unless it is supported by other initiatives. However, recent developments in Cyprus relating to greater education as to the benefits of corporate governance, as well as more stringent listing rules for companies lacking aspects of corporate governance, suggest that Cyprus is making serious endeavours to improve the corporate governance of its listed companies.
Keywords: Compliance; Corporate governance; Cyprus